Pedagogi Kesabaran dalam Al-Qur’an: Suatu Kajian Eksegetis terhadap Surah al-Baqarah Ayat 153–157 - NURUL HAYATI (Educational Research Center, 2025)
Abstract. This article explores the dimensions of patience education (ṣabr) as articulated in Surah al-Baqarah, verses 153–157, which constitute a significant discourse on resilience, spiritual steadfastness, and divine guidance within the Qur’anic worldview. The study is motivated by the urgent need to reconsider the theological and pedagogical significance of patience amidst contemporary global challenges such as socio-political instability, mental health crises, and educational transformation. Employing library research combined with content analysis, this inquiry examines both classical and modern exegesis as well as comparative educational theories to uncover the multilayered meanings of the text. Findings reveal that patience in these verses is not merely a theological obligation but also a pedagogical principle that nurtures holistic human development—integrating faith, cognition, and emotional resilience. The verses emphasize patience as an active and constructive response to trials, reinforced through remembrance of God and collective solidarity within the faith community. Theoretically, this study contributes to Qur’anic pedagogy by positioning ṣabr as the foundation of character education and moral development. Practically, it offers insights for contemporary education by framing patience as a transformative instrument for personal growth, conflict resolution, and socio-religious resilience. By bridging Qur’anic hermeneutics and educational discourse, this study provides both a renewed conceptual framework and a practical model for integrating the education of patience into formal and informal learning systems.